Creating functionally graded concrete materials with varying 3D printing parameters. Issue 3 (3rd July 2022) - Tay, Yi Wei Daniel; Lim, Jian Hui; Li, Mingyang; Tan, Ming Jen
ABSTRACT: The varying physical property in a functionally graded material can be tailored to its specific requirements while using material resources effectively. 3D concrete printing can produce robust and lightweight functionally graded material for the construction industry. In this study, an approach was developed to create an objective tailored functionally graded concrete material by examining the filament material property correlations with the printing parameters. It was found that the physical property of the printed material is closely correlated to the flow rate and travel speed of the printer. Results obtained from the experiment show that the optimised structure achieved an approximately 50% improvement in the strength-to-weight ratio. This preliminary examination of the 2D optimised concrete structure opens the realm of possibility for future work in 3D optimised functionally graded concrete.